Expenditure-based segmentation of foreign visitors in a nature reserve in Tokyo, Japan / Hasan Zakaria, Shinya Numata and Katsuya Hihara - Zakaria, Hasan; Numata, Shinya; Hihara, Katsuya (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2021)
The study examined the expenditure, socio-demographic and trip characteristics of foreign visitors to a popular nature reserve in Tokyo, Mount Takao. 742 respondents completed surveys during low and peak seasons. Heavy, medium and light expenditure segments were distinguished. Statistically significant differences were found in socio-demographic and trip characteristics among the segments. Specifically, the results revealed significant differences in the status of foreign visitors, travel companions, repeat visitation rate, and visiting season among the three expenditure segments. Heavy spenders were more likely to be the foreign tourists travelling as a couple, first-time visitors during peak season. The identification of the characteristics of different spender segments is expected to contribute to the development of targeted marketing strategies to attract heavy spenders, facilitate the management of resources, and inform strategies to encourage spending by visitors in the light and medium expenditure segments.